Evaluation of powder-layering vs. spray-coating techniques in the manufacturing of a swellable/erodible pulsatile delivery system. (2nd August 2020) - Foppoli, Anastasia; Cerea, Matteo; Palugan, Luca; Zema, Lucia; Melocchi, Alice; Maroni, Alessandra; Gazzaniga, Andrea
Abstract: A swellable/erodible system for oral time-dependent release, demonstrated to provide consistent pulsatile and colonic delivery performance, has been manufactured through a range of coating techniques to achieve the functional hydroxypropyl methylcellulose (HPMC) layer. Although aqueous spray-coating has long been preferred, the processing times and yields still represent open issues, especially in view of the considerable amount of polymer required to give in vivo lag phases of proper duration. To make manufacturing of the delivery system more cost-efficient, different coating modes were thus evaluated, namely top and tangential spray-coating as well as powder-layering, using a fluid bed equipment. To this aim, disintegrating tablets of 5 mm in diameter, containing a tracer drug, were coated up to 50% weight gain with low-viscosity HPMC, either as a water solution or as a powder formulation. In all cases, process feasibility was assessed following setup of the operating conditions. Irrespective of the technique employed, the resulting dosage forms exhibited uniform coating layers able to defer the onset of release as a function of the amount of polymer applied. The structure and thickness of such layers differed depending on the deposition modes. With respect to top spray-, both tangential spray-coating and powder-layering were shown to remarkably ameliorate the process time, which was reduced to approximately 1/3 and 1/6, and to enhance the yield by almost 20 and 30%, respectively. Clear advantages associated with such techniques were thus highlighted, particularly with respect to powder-layering here newly proposed for application of a swellable hydrophilic cellulose derivative.